Palliative and end-of-life care’s barriers for older adults - Indarwati, Retno; Fauziningtyas, Rista; Kuncahyo, Gilang Dwi; Tristiana, Rr Dian; Chong, Mei Chan; Smith, Graeme D. (Emerald, 2020)
Purpose: A nursing home is a place that is familiar with death, since many older adults will spend the latter part of their lives in such a setting. However, research on this topic is still limited, especially in Indonesia. The purpose of this paper is to explore the barriers to successful palliative and, more generally, end-of-life care (EOLC) for older adults in nursing homes and to explore nurses’ views on the subject. Design/methodology/approach: The study is of a qualitative nature and it employs a phenomenological approach. In-depth interviews with 15 nurses who taken care of older adults in a nursing home were conducted. The data were analysed using thematic content analysis. Findings: Barriers to effective EOLC include lack of knowledge, ineffectual communication and insufficient resources. Research limitations/implications: Better policies are needed, especially in training related to palliative/EOLC subjects and equitable distribution of professional health workers to overcome the barriers. The government should also encourage collaboration involving hospitals, Puskesmas (Health Centre Services), community and resident care settings in sharing knowledge and skills, especially for nurses. Originality/value: The barriers identified in palliative and EOLC have been found to be almost identical to those encountered in other health services. © 2019, Emerald Publishing Limited.